Exerkines and myokines in aging sarcopenia - Wang, Huan; He, Wenbi; Chen, Peishan; Wang, Haozhe; Wang, Huiguo; Zhu, Lin; Liu, Xiaoguang (Frontiers in Endocrinology, 2025)
Aging sarcopenia is an unavoidable condition that affects the majority of older adults in their later years. Exercise has been extensively researched as an effective intervention for sarcopenia. In particular, the release of exerkines and myokines during physical activity has beneficial effects on the body, which, as mediators, offer a novel therapeutic strategy for elucidating how exercise enhances skeletal muscle mass and function. In this review article, we summarize how exerkines exert protective effects on aging skeletal muscle mainly through the following mechanisms: (1) mediating energy diversion to skeletal muscle, ensuring more energy supply to the muscle; (2) enhancing the activity of skeletal muscle satellite cells to promote muscle repair and regeneration; (3) upregulating the expression of genes associated with muscle regeneration and, at the same time, inhibiting the expression of those genes that contribute to the atrophy of skeletal muscle; and (4) improving the function of the neuromuscular junction to improve the neural control of skeletal muscle. These combined effects constitute the protective mechanism of myokines on aging skeletal muscle.